2015
DOI: 10.3389/fmicb.2015.00870
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of oosporein isolated from endophytic fungus Cochliobolus kusanoi

Abstract: In the present study, oosporein, a fungal toxic secondary metabolite known to be a toxic agent causing chronic disorders in animals, was isolated from fungus Cochliobolus kusanoi of Nerium oleander L. Toxic effects of oosporein and the possible mechanisms of cytotoxicity as well as the role of oxidative stress in cytotoxicity to Madin-Darby canine kidney kidney cells and RAW 264.7 splene cells were evaluated in vitro. Also to know the possible in vivo toxic effects of oosporein on kidney and spleen, Balb/C mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 41 publications
1
6
0
1
Order By: Relevance
“…The cytotoxicity of oosporein was evaluated toward A549 and presented the IC 50 value of 21 μM (Alurappa et al, 2014 ). The cytotoxic potential of oosporein in the MDCK cell line and its role in oxidative stress in vivo and in vitro have been previously reported by our research group (Ramesha et al, 2015 ).…”
Section: Cytotoxic Compounds From Endophytic Fungi Associated With Tesupporting
confidence: 60%
“…The cytotoxicity of oosporein was evaluated toward A549 and presented the IC 50 value of 21 μM (Alurappa et al, 2014 ). The cytotoxic potential of oosporein in the MDCK cell line and its role in oxidative stress in vivo and in vitro have been previously reported by our research group (Ramesha et al, 2015 ).…”
Section: Cytotoxic Compounds From Endophytic Fungi Associated With Tesupporting
confidence: 60%
“…Oosporein produced by B. caledonica has immunosuppressive properties and contributes to greater and faster mortality of insects (Mc Namara et al 2019). Oosporein from Cochliobolus kusanoi exerts cytotoxic effects on Madin-Darby canine kidney (MDCK) and mouse macrophage (RAW 264.7), which is mediated by ROS through oxidative stress that increases lipid peroxidation and glutathione (GSH) level (Ramesha et al 2015).…”
Section: Secondary Metabolites: Role In Infection and Possible Applicmentioning
confidence: 99%
“…However, the confirmation of oosporein production in C. cicadae indicates that this fungus could potentially cause avian gout or mortality in chickens and birds [ 53 , 54 ]. Previous in vivo and in vitro assays also indicated that oosporein could cause cytotoxicity in the canine kidney and lead to tissue damages in mice in a dose-dependent manner by inducing oxidative stress [ 55 ]. In addition, our transcriptomic and metabolomic data indicated that the oxalic acid (OS) biosynthetic pathway was up-regulated during fungal fruiting, and OS was more highly accumulated in the fruiting-body samples when compared to the liquid cultures.…”
Section: Discussionmentioning
confidence: 99%